Informing Policy with Agricultural Research-for-Development: Insights from Research on Resilience - Kramer, Berber (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
• Limited access to credit, e.g., due to a lack of collateral and documented land rights, exposes smallholder farmers to risk and liquidity constraints • This does not only reduce farmers’ ability to cope with weather shocks but may also prevent them from investing in their farms. • Insurance to reduce risk and thereby increase access to credit typically falls short: High costs of indemnity-based insurance; Basis risk in weather index-based insurance. • What if we can overcome information asymmetries at a low cost, using smartphone images?